Legal Pluralism as a Theory for the Challenges on Environmental Health - Ronald Ralf Becerra Rodríguez (Opinión Jurídica)
This paper intends to justify the theory of legal pluralism for studying environmental health issues. The positive law approach has made some headway, although some areas of environmental health seem to be incipient. Hard law has encountered difficulties to succeed in enforcing industrial pollution or water contamination. Furthermore, national jurisdictions are prone to support particular economic interests. This conundrum of legal positivism encourages challenging it with the theory of pluralism. It is found that the latter might allow deliberation and active participation of non-state actors within environmental health. It is also discussed that the plurality of law allows certain flexibility due to its little hierarchization, the lack of theoretical rules and the relaxation of state sovereignty.